(untitled) (Mongolian Journal of Agricultural Sciences, 2017)
Maize is the one of the world leading crop. 90% of the maize produced in industrialized countries is grown in temperate production environments which mean that Mongolia has potential to grow maize plant. Three open-pollinated varieties (OPV) were studied in Institute of Plant and Agricultural Sciences to compare growing potential under non-irrigated condition. Mongolian corn population showed high significance than the other two on yield related traits, ear length, kernel length, fresh ear weight, tassel length and number of kernel per row. The result showed that studied OPV can yield under rain-fed condition and can be distributed to the farmers.